The Role of Zakat and Taxes on Economic Growth - Mansur, Ahmad; Kafabih, Abdullah; Hakim, Abdul; Fuad, Lian (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This conceptual study aims to investigate the synergistic roles of zakat and taxation as fiscal instruments to promote equitable income distribution and foster economic growth within the framework of Islamic economics. Grounded in descriptive qualitative analysis and literature review, the research outlines how zakat and tax policies can be integrated to form a more just and sustainable fiscal structure. While taxes are recognized as essential for state financing and macroeconomic stabilization, zakat—though traditionally religious in nature—emerges as a viable counter-cyclical tool to support poverty alleviation, enhance purchasing power, and drive inclusive development. The study highlights the distinct yet complementary characteristics of zakat and taxes, emphasizing their potential to correct wealth disparities and stimulate productive investment through multiplier effects. By embedding Islamic moral values such as moderation, social justice, and prohibition of usury, this research offers an alternative paradigm for fiscal governance. The study contributes to global economic scholarship by presenting a faith-based fiscal model that may inform public finance policies in Muslim-majority countries and beyond. Future research is recommended to develop empirical models that quantify the macroeconomic impacts of zakat-tax integration and explore its application in diverse economic contexts.